Exploration of the views of traditional healers regarding the Termination of Pregnancy (TOP) law - MA Rakhudu; AMM Mmelesi; CPH Myburgh; M Poggenpoel (AOSIS, 2006)
The North-West Province is predominantly a rural area, and traditional healers remain the most important and influential members of the rural communities. A qualitative, explorative, descriptive and contextual research design was used. In-depth, individual focused and interactive interviews were held with eight traditional healers from the rural areas of Mmabatho-Mafikeng. In addition, field notes and observations were utilised. The objective of this article is to explore the views of the traditional healers regarding termination of pregnancy (TOP) law. The results reflected the following themes: termination of pregnancy is killing; a child is a precious gift from God and the ancestors; there are alternatives to TOP; people who had any type of abortion should be cleansed with "dipitsa" or herbs; TOP may be allowed only in case of rape and incest, rape and incest offenders should be severely punished; and the traditional healers were not consulted during formulation of the TOP Law. It is therefore recommended that traditional should be involved in TOP workshops and educational programmes to enable them to provide counselling before and after abortion.